PELAKSANAAN LAYANAN BIMBINGAN KELOMPOK DENGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN PEMAHAMAN BAHAYA NARKOBA PADA SISWA - Mutiara Sari Tobing; Yeni Karneli; Nurfarhanah Nurfarhanah; Rezki Hariko (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research aims to analyze the effectiveness of group guidance services using audio-visual media to increase students' understanding of the dangers of drugs. This research uses quantitative methods with an experimental type. The population in this study was 115 with the selected samples being 10 experimental groups and 10 control groups taken using simple random sampling techniques. The research results show that group guidance services using audio-visual media have proven effective in increasing students' understanding of the dangers of drugs. The increase in post test results for the experimental group was higher than that of the control group, which is proof that this research was successful. This increase proves that group guidance using audio-visual media is effective. Then the results of the hypothesis test also stated that there was an influence provided by group guidance using audio-visual media on students' understanding of the dangers of drugs.